2020
DOI: 10.1002/hep.31459
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Virome in Patients With Alcoholic Hepatitis

Abstract: BaCKgRoUND aND aIMS: Alcoholic hepatitis (AH) is a severe manifestation of alcohol-associated liver disease (ALD) with high mortality. Although gut bacteria and fungi modulate disease severity, little is known about the effects of the viral microbiome (virome) in patients with ALD. appRoaCH aND ReSUltS: We extracted virus-like particles from 89 patients with AH who were enrolled in a multicenter observational study, 36 with alcohol use disorder (AUD), and 17 persons without AUD (controls). Virus-like particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 59 publications
(92 reference statements)
2
80
0
3
Order By: Relevance
“…Herpesviridae, as well as Staphylococcus phages, were associated with higher MELD scores and increased mortality [29]. Other bacteriophages were more abundant in the AH group, including…”
Section: Intestinal Virome Changes In Patients With Alcohol Related Lmentioning
confidence: 93%
See 3 more Smart Citations
“…Herpesviridae, as well as Staphylococcus phages, were associated with higher MELD scores and increased mortality [29]. Other bacteriophages were more abundant in the AH group, including…”
Section: Intestinal Virome Changes In Patients With Alcohol Related Lmentioning
confidence: 93%
“…Escherichia-, Enterobacteria-, and Enterococcus phages [29]. In contrast to bacterial and fungal J o u r n a l P r e -p r o o f diversity, viral diversity was increased in patients in alcohol consuming groups, and is most pronounced in patients with AH [29]. This may be attributed to phage-bacteria dynamics and incorporation of phage genetic material into their bacterial hosts.…”
Section: Intestinal Virome Changes In Patients With Alcohol Related Lmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies showed that alcohol consumption is associated with decreased bacterial diversity and altered gut microbiome in animal models and human patients [83,84]. Furthermore, intestinal virome characterization showed an increased viral diversity in fecal samples from patients with ALD compared with nonalcoholic controls, and altered viral taxa are associated with disease severity and mortality in alcoholic hepatitis patients [85]. Research in the field of mycobiome showed changes in the composition of fecal mycobiome in patients with ALD compared with non-alcoholic controls.…”
Section: Mycobiome and Alcohol-associated Liver Diseasementioning
confidence: 99%